Development and Validation of a Portable Human Body Joint Power Test System - Lin Li; Zhongqiu Ji; Ye Xia; Rui Gong (International Journal of Distributed Sensor Networks)
A portable human body joint power test system was developed using inertial sensor technology and wireless Bluetooth acquisition technology. A detailed description of the internal structure of the system and the data processing method involved is provided. The test system uses the cubic spline interpolation method, which is very convenient for obtaining the maximum peak points of muscle isotonic contraction joint power curves under different loads. Moreover, the system is portable and can be deployed in the classroom and the playground for education and testing. The test system is very useful in many respects, such as athlete selection and daily strength training. We established a model of our subject using a balanced proportion scaling method in the inverse dynamics software AnyBody modeling system. The muscle model uses the Hill muscle model. The data import interface program was written in the parameterized model definition language AnyScript to import data. The raw data was smoothed with a Butterworth low-pass filter. Dumbbell curl simulation was conducted in AnyBody. The results of the simulation and those of the real test system were tested using the paired samples t -test method; the value of Sig was determined to be greater than 0.05, indicating no significant difference and that the data of the test system are valid.